PHYSICAL AND PSYCHO-SOCIALENVIRONMENTSSTRATEGIES INMANAGING ENGLISH CLASSES FOR YOUNG LEARNERS - Ubaedillah, Ubaedillah; Hartono, Rudi (English Education Journal, 2016)
One of the biggest challenges faced by teachers of young learners is classroom management. The major reasons of the challenges were negative student attitudes and discipline (Wragg, 2001; Linse, 2005). This study describes physical and psycho-social environments in managing English classes for young learnersâ (a case study at PelitaBangsa elementary school in Cirebon year 2016). Objectives of this study are exploring the implementation of physical and psycho-socialenvironments in managing English classes for young learners. This is a case study which involved an English teacher and 30 students from 2 classes at PelitaBangsa elementary school in Cirebon. The data were gained from classroom observations, questionnaires, and interviews. This study used observational design. The approach used in this research was the qualitative one supported by simple statistic calculation (percentage) in order to support the findings.Based on the data collection, the study revealed five findings. First, the implementation of of physical environment in managing English classes for young learners was determined depending on the learning activities. Second, psycho-social environmentwas implemented based on the studentsâ need. Third, there were relations between physical and psycho-social environmentsin managing English classes for young learners. Fourth, studentsâ perception about teacherâs classroom management can be categorized in strong category. Fifth, generally, the major reasons for applying those classroom managements were concluded into two, which include: (1) because physical and psycho-social environments were essential to control studentsâ behavior in the classroom, and (2) because bothof classroom management were beneficial to facilitate students in learning English.